PENGARUH PEMBERIAN UREA TERHADAP LAJU DEKOMPOSISI SERASAH TEBU DI PUSAT PENELITIAN GULA JENGKOL, KABUPATEN KEDIRI - Reni Wijayanti; Budi Prasetya (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Application of urea will increase nitrogen content and microorganism activity so it can decrease C/N ratio. Sugarcane residues is low quality organic matter source and it is difficult to decompose. Accelerating the rate of decomposition of sugarcane residues can be done byh enumeration and application of urea fertilizer on sugarcane residues. The purpose of this study was to find out the effect of urea application on decomposition rate of sugarcane residues with enumeration on trash management system. The study was conducted at HGU C-13 PG Pesantren Baru Garden, Kediri Regency at 4.5-month sugarcane plantation. The experiment was designed using a randomized block design with six treatments and four replications. The treatments used were ratoon sugarcane which was trash chopped (dry and pure sugarcane litter) and urea. The doses of urea added to each treatment were Control (without urea); P1 (urea 2 kg ha-1); P2 (urea 3 kg ha-1); P3 (urea 4 kg ha-1); P4 (urea 5 kg ha-1); and P5 (urea 6 kg ha-1). The results showed that the addition of urea with dose 4 kg ha-1 to sugarcane residues decreased the C/N ratio by 10,94% compared to control and increased N-total by 16,00% as well as microbial population by 25,00%.